2017
DOI: 10.1111/mve.12283
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence and seasonal and environmental distributions of the sandflies Lutzomyia longipalpis and Nyssomyia whitmani in the city of Puerto Iguazú, northeastern Argentina

Abstract: The aim of this work was to study the distribution of Phlebotominae (Diptera: Psycodidade) abundance in time and space in an area in northeastern Argentina with vector transmission of visceral and tegumentary leishmaniasis. For this, 51 households were selected using a 'worst scenario' criterion where one light trap was set during two consecutive nights in peridomiciles in the transitions between the four seasons, and the environment was surveyed simultaneously. The relationships of phlebotomine assemblage str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 34 publications
(59 reference statements)
1
21
0
1
Order By: Relevance
“…longipalpis and periurban-rural Ny. whitmani in the area of the Argentina-Brazil-Paraguay border has already been described [29,42]. The rarefaction curves suggest that the peridomestic environment in rural landscapes seems stable and homogeneous enough to make the captures representative of their phlebotomine assemblages.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…longipalpis and periurban-rural Ny. whitmani in the area of the Argentina-Brazil-Paraguay border has already been described [29,42]. The rarefaction curves suggest that the peridomestic environment in rural landscapes seems stable and homogeneous enough to make the captures representative of their phlebotomine assemblages.…”
Section: Discussionmentioning
confidence: 79%
“…To describe the forestrelated populations properly a greater capture effort is required, but also a differentiated strategy of trapping due to the different strata in altitude related to the canopy, the lack of blood sources nearby the placement of traps that could affect the captures. Therefore, to avoid sporadic or unrepresented species in the modeling, only the well-represented species were analysed [15,17,46]. Thus, phlebotomine diversity both in rural and urban environments is related to the heterogeneity of the landscape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of individuals obtained from both species is very low, but the climate conditions according to the records during the study were not optimal for the activity of phlebotomines 17 . Even though the scenario is adverse and there is eventual recent colonization, Lu.…”
Section: Discussionmentioning
confidence: 90%
“…The extruded collar formulation used in this study provides extended deltamethrin release and is a key factor in the observed 12 month duration of anti-feeding efficacy. This extended duration of protection that could allow just once yearly treatment can be particularly relevant in geographies, for instance in areas of South America, where phlebotomine flies present an almost year-long risk of transmission of L. infantum [ 26 , 27 ]. Additionally, recent evaluation of long-acting ectoparasiticides has shown that increasing the duration of protection leads to increased owner compliance and therefore more months of protection during the year [ 28 ].…”
Section: Discussionmentioning
confidence: 99%